Challenges and Advances in Managing Heatstroke Among Military Forces: A Review of Recent Studies - Fransiska Pratiwi, Ardita (Syntax Corporation, 2026)
Exertional heat stroke (EHS) remains a persistent threat to military operations, necessitating a shift from traditional thermal load perspectives toward a